2007
DOI: 10.4049/jimmunol.179.10.6715
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Colony-Stimulating Factor 1 Can Be Cleaved by TNF-α Converting Enzyme or Endocytosed in a Clathrin-Dependent Manner

Abstract: CSF-1 is a hemopoietic growth factor, which plays an essential role in macrophage and osteoclast development. Alternative splice variants of CSF-1 are synthesized as soluble or membrane-anchored molecules, although membrane CSF-1 (mCSF-1) can be cleaved from the cell membrane to become soluble CSF-1. The activities involved in this proteolytic processing, also referred to as ectodomain shedding, remain poorly characterized. In the present study, we examined the properties of the mCSF-1 sheddase in cell-based a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 79 publications
1
30
0
Order By: Relevance
“…MMP14 and ADAM10 are known to convert transmembrane molecules into a soluble form through a proteolytic process called ectodomain shedding, and they also share common substrates (35,36). In addition, it has also been shown that a close relative and functionally similar protease to ADAM10, ADAM17 (37), can induce proteolytic processing and shedding of macrophage colony-stimulating factor (M-CSF) (38). M-CSF is a cytokine that promotes the release of proinflammatory chemokines and has an important role in innate immunity and in inflammatory processes.…”
Section: Intracellular Lps Stimulation Activates Strong Vesicle-mediamentioning
confidence: 99%
“…MMP14 and ADAM10 are known to convert transmembrane molecules into a soluble form through a proteolytic process called ectodomain shedding, and they also share common substrates (35,36). In addition, it has also been shown that a close relative and functionally similar protease to ADAM10, ADAM17 (37), can induce proteolytic processing and shedding of macrophage colony-stimulating factor (M-CSF) (38). M-CSF is a cytokine that promotes the release of proinflammatory chemokines and has an important role in innate immunity and in inflammatory processes.…”
Section: Intracellular Lps Stimulation Activates Strong Vesicle-mediamentioning
confidence: 99%
“…However, there are several cytokines (such as the cell surface isoform of colony stimulating factor-1) that are active in both their membrane-bound form and their soluble form. 44,45 Some receptors, including vascular growth factor receptor 2 and c-Kit, are also subjected to ectodomain shedding, 46,47 and in theory, the cleavage of these receptors results in the down-regulation of the availability of these receptors and, consequently, signaling through these receptors. In contrast, the interleukin 6 receptor, which has also been shown to be released by TACE, acts as a functional soluble receptor via binding to interleukin 6 and gp130.…”
Section: What Is the Function Of Ectodomain Shedding In General?mentioning
confidence: 99%
“…Some members of the PDGF ( platelet-derived growth factor) receptor subfamily are regulated by ligand shedding, including cKit/SCFR , FLT3/Flk2 ), and CSF1R/Ems (Horiuchi et al 2007b). These RTK pathways play important immune roles including regulating haematopoiesis (cKit and FLT3) (Ashman 1999;Naoe and Kiyoi 2004) or macrophage and osteoclast development (CSF1R) (Cecchini et al 1997).…”
Section: Shedding Of Ligands Of the Pdgf Familymentioning
confidence: 99%